Analisis Variabel-variabel yang Memengaruhi Insiden Tuberkulosis di Provinsi Jawa Timur Tahun 2022 - Karim, Abdul; Utomo, Agung Priyo (Seminar Nasional Official Statistics, 2024)
Tuberculosis is one of the most dangerous infectious diseases in the world and is still a major problem in Indonesia. In 2022, the number of tuberculosis cases in East Java became the second highest nationally and became the province with the highest increase in tuberculosis incidence in Indonesia. This study aims to model the incidence of tuberculosis in East Java Province in 2022. The data used originated from the Central Statistics Agency (BPS) of East Java and the East Java Provincial Health Office. The Robust MM-Estimator method is used in this study. The results showed that the population density variables, the average number of cigarettes per week smoked by residents aged 5 years and older who smoked tobacco, and the number of new OD-HIV cases were found to have a significant positive effect on the incidence of tuberculosis in East Java.. The variable of the percentage of households with a floor area per capita ≤ 7.2 m2 had a significant negative effect on the incidence of tuberculosis in East Java.